Library collections Among Selection Policy, Evaluation Criteria, Organization and Maintenance - Kadhim Hantoush, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to clarify what the Library collections are, in terms of types and shapes, also to know the methods that were used in evaluating the library collection in the libraries and information centers, regardless the type of library whether it is children’s libraries, school libraries, public libraries, university libraries or specialized libraries as well as electronic information sources which are available within the library collection , knowing the selection policy ,its motives and tools that the library uses them acquire the appropriate sources of information for its collection and its suitability to the needs of the beneficiaries, knowing their opinions and the extent of benefiting from their use of the sources of the information which are in the library, in addition, the operations of preserving, organizing, maintaining, perpetuating library collection , the processes of exclusion of sources that are not beneficial, diagnosing strengths and upgrading them, as well as weaknesses points and developing appropriate solutions for them, developing appropriate suggestions to develop them and bring them in line with scientific development , research and study needs.